Development of Interactive E-Module Based on Papuan Local Wisdom on Basic Mathematics Course - Paskha Marini Thana,; Khumaeroh Dwi Nur'aini,; Dessy Riski Suryani, (Technium Social Sciences Journal, 2023)
Lecturers have an important role in facilitating technology-based learning activities. A common problem is the lecturer's habit of using monotonous teaching media that makes students bored in Mathematics class. Therefore, researchers took steps to develop teaching materials in the form of interactive e-module based on local wisdom of Papua or Merauke on basic mathematics course. E-modules are developed by utilizing the Heyzine flipbooks application which is integrated with the wordwall.net application. The research method used is R & D, the 4D development model which has stages such as Define, Design, Develop, and Disseminate. Data collection techniques are observation and questionnaires. The questionnaire used consists of three types, which are material expert, media expert, and student (user) questionnaires. Based on the assessment of media expert and material expert validators, the average feasibility of 3.48 and 3.36 was obtained, as well as the results of trials conducted on students on average 3.34, it can be concluded that the e-module developed is valid and feasible to use.